Anthropometric Indices as Indicators of Obesity of Children from Elementary School in Montenegro - Pavle Malovic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2019)
The aim of this research was to determine anthropometric indices as indicators of obesity of children in Montenegro. The research involved 135 children from Montenegro and sample of examinees is divided into two sub-samples. The fi rst sub-sample of the examinees consisted of 66 boys aged 7-8 years from Nikšić and Kotor, while the other sub-sample consisted of 69 girls also aged 7-8 years from Niksic and Kotor. Anthropometric characteristics were evaluated by a battery of 4 variables: body height, body weight, waist and hip circumference. Mentioned variables were used to calculate following anthropometric indices which gave as informations about obesity: Body mass index (BMI), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR). The standard central and dispersive parameters of all variables are calculated. The signifi cance of the diff erences between the children in the ratios was determined by a t-test for small independent samples. It was not found that the children with diff erent gender have statistically signifi cant diff erences in analyzed ratios as indicators of obesity. Thus, it was found that 16.3% of children were obese and those results will help us to realize that we have to adequately aff ect on detected problem.